KONDISI LINGKUNGAN PERAIRAN BUDIDAYA RUMPUT LAUT EUCHEMA SPINOSUM DI DESA BONEATIRO BARAT KABUPATEN BUTON - Waode Sitti Cahyani; Bahtiar Hamar; Nabil Zurba; Eca Farman Kabaena (Journal of Aceh Aquatic Sciences, 2021)
Seaweed is one of the leading commodities in Indonesia. National aquaculture production for export focuses on 3 commodities that is shrimp, lobster and seaweed, where the highest aquaculture production is seaweed. The value of aquaculture for seaweed commodities in 2015–2020 increased by 4.9%, while the target of seaweed commodities for export in 2020-2024 has increased by 2,154,000 (tons), where in 2010 the number of export commodities was 10,298,000 (tons) to 12,452,000 (tons) in 2024 (KKP). Southeast Sulawesi ranks 5th as the government's priority location for achieving seaweed production in 2020-2024 after South Sulawesi, East Nusa Tenggara, Central Sulawesi, West Nusa Tenggara (KKP, 2021). One of the centers of seaweed production in Southeast Sulawesi is Buton Regency. West Boneatiro Village is located in Kapontori District, Buton Regency which is currently redeveloping the cultivation of seaweed Euchema spinosum which was stopped about 10 years ago because decrease in water quality which causes crop failure. The results of this study are expected to provide information to local fishermen regarding water quality for the suitability of Euchema spinosumseaweed cultivation.